Risk-based VAT planning model: optimizing compliance and VAT savings - Sri Setia Ningsih; Yanti Budiasih; Lestari Adhi Widyowati (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
This study develops a risk-based VAT tax planning model that emphasizes tax compliance as a mediating variable in optimizing tax savings in construction companies. Using a sequential explanatory mixed-method design, quantitative data were collected through questionnaires from 60 respondents representing medium-sized construction firms in the City of Tangerang, followed by a focus group discussion with tax consultants to support model interpretation. Sixteen hypotheses were tested using path analysis. The results indicate that all VAT planning components timely VAT reporting, optimization of input tax crediting, delay in tax invoice issuance, postponement of input tax crediting, and the selection of restitution or compensation schemes, have a significant effect on tax compliance. However, only strategic variables, namely delaying tax invoice issuance and selecting restitution or compensation schemes, have a significant direct effect on optimizing tax savings. Other administrative strategies affect tax savings indirectly through tax compliance. Tax compliance itself has a significant positive effect on VAT savings optimization and partially mediates the relationship between VAT planning practices and tax savings. This study introduces a risk-based, compliance-oriented VAT planning model that supports sustainable VAT savings and recommends integrating compliance risk management into VAT planning and administrative practices.